2022
DOI: 10.1186/s12891-022-05764-1
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ perspectives on the benefits of feedback on patient-reported outcome measures in a web-based personalized decision report for hip and knee osteoarthritis

Abstract: Background Applications of patient-reported outcome measures (PROMs) for individual patient management are expanding with the support of digital tools. Providing PROM-based information to patients can potentially improve care experiences and outcomes through informing and activating patients. This study explored patients’ perspectives on the benefits of receiving feedback on PROMs in the context of a web-based personalized decision report to guide care for their hip or knee osteoarthritis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…In line with other research on receiving health information, patients' challenges with understanding specific information are not incompatible with perceiving overall benefits 41 . In our companion work, we identified that—notwithstanding the challenges specified in this paper—patients perceived multiple actual or hypothetical benefits of PRO‐based feedback in this report, including increased knowledge about their health status, enhanced communication with the surgeon, and increased confidence and trust 20 . Since this report was developed, similar PRO‐based reports have been developed with completed or proposed quantitative evaluations of patients' decision quality 16–18,42 .…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…In line with other research on receiving health information, patients' challenges with understanding specific information are not incompatible with perceiving overall benefits 41 . In our companion work, we identified that—notwithstanding the challenges specified in this paper—patients perceived multiple actual or hypothetical benefits of PRO‐based feedback in this report, including increased knowledge about their health status, enhanced communication with the surgeon, and increased confidence and trust 20 . Since this report was developed, similar PRO‐based reports have been developed with completed or proposed quantitative evaluations of patients' decision quality 16–18,42 .…”
Section: Discussionsupporting
confidence: 77%
“…41 In our companion work, we identified that-notwithstanding the challenges specified in this paper-patients perceived multiple actual or hypothetical benefits of PRO-based feedback in this report, including increased knowledge about their health status, enhanced communication with the surgeon, and increased confidence and trust. 20 Since this report was developed, similar PRO-based reports have been developed with completed or proposed quantitative evaluations of patients' decision quality. [16][17][18]42 These reports are heterogeneous, with some including explicit preference elicitation or values clarification modules.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since strict risk cutoffs may exacerbate disparities, PROM-guided decision-making has implications for equity 58 . Additionally, the incorporation of patient-facing PROM information in preoperative counseling may help patients to better understand their current health status and to shape expectations about postoperative status, thereby informing patient preferences for decision-making 59,60 . One study found that a non-PROM-based decision aid increased total knee arthroplasty utilization in Black Data capture Operationalizing the same collection schedule for all patients with a condition/procedure but offering remote electronic and in-clinic options for data collection (e.g., on a tablet, or even on paper if technological literacy is a substantial barrier)…”
Section: Meaningful Applicationmentioning
confidence: 99%